2014
DOI: 10.1021/ie5023145
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Properties of Injection Molded Microcellular Poly(ether imide) (PEI)/Polypropylene (PP) Foams

Abstract: A series of PEI/PP blends were injection molded by conventional and microcellular methods. Polypropylene (PP) was selected as the disperse phase in order to improve the cell nucleation of poly(ether imide) (PEI)/PP blends. The effect of the PP content on the morphology of the PEI/PP blends or foams, the mechanical, thermal and dielectric properties was investigated. In the immiscible PEI/PP blends, the cell density of microcellular PEI/PP foams increased greatly with the increasing of the content of PP because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…However, the coalescence and even the collapse of the cells will be caused by the excessive high foaming temperature (>250 °C) and long foaming time (>300 s). Besides, many studies about high melt viscosity branching have been reported to improve the cellular structure of the foamed PP . However, the researches on the relationship between structure and thermal conductivity of foamed PP were very limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, the coalescence and even the collapse of the cells will be caused by the excessive high foaming temperature (>250 °C) and long foaming time (>300 s). Besides, many studies about high melt viscosity branching have been reported to improve the cellular structure of the foamed PP . However, the researches on the relationship between structure and thermal conductivity of foamed PP were very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The cell density ( Nf), number of cells per cubic centimeter of the foams, was calculated by eq. : Nf=(nΑ)32true(11Vftrue) where n is the number of cells on the SEM micrograph, A is the area of the micrograph (cm 2 ), and Vf is the void fraction of the foamed sample, which can be estimated as Vf=1ρfρ where ρf is the density of foamed samples, and ρ is the mass density of unfoamed samples.…”
Section: Methodsmentioning
confidence: 99%
“…In order to achieve good foamability in a thermoplastic polymeric composition, knowledge of its most two important aspects, namely, rheological and morphological properties are inevitable. Dispersion and morphology are very crucial for foam nucleation; whereas, rheology of the polymer dictates not only the polymeric compositional morphology, but also the growth process in foaming and ultimately establishes the final foam morphology . Cell nucleation is dependent on the critical size and total surface area of the inclusion inside matrix; on contrary, cell growth depends on the viscoelastic characteristics of the whole polymeric composition …”
Section: Introductionmentioning
confidence: 99%